Self-floating beta-ketoenamine covalent organic framework-chitosan aerogel adsorbent as well as preparation method and application thereof

Through the use of self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent, the stability and selectivity of existing adsorbent materials in acidic and highly competitive ion environments are solved, and precious metals are realized. Efficient and fast recycling, and reduces the cumbersomeness and cost of recycling steps.

CN119406384APending Publication Date: 2025-02-11CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411735711.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing adsorbent materials are difficult to meet the stability and selectivity requirements of acidic solutions and high competitive ion environments when dealing with electronic waste, and the recycling steps of precious metal ions are cumbersome and costly.

Method used

The self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent is adopted. This material converts light energy into thermal energy to achieve stable and rapid selective adsorption of precious metals, and the adsorbed precious metals under photocatalysis Ion reduction to metal element.

Benefits of technology

This adsorbent exhibits high adsorption capacity and selectivity within a wide range of pH application, exhibits efficient adsorption and recovery performance for Au, and has a mild process and low cost, making it suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406384A_ABST
    Figure CN119406384A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorbents, in particular to a self-floating beta-ketoenamine covalent organic framework-chitosan aerogel adsorbent as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, preparing the TpPa-1-COF nano particles; s2, ultrasonically dissolving CS in an acetic acid aqueous solution to obtain a CS acetic acid aqueous solution; s3, performing ultrasonic dispersion on the TpPa-1-COF nanoparticles in ultrapure water, and then uniformly mixing a COF aqueous solution with a CS acetic acid aqueous solution to obtain a COF / CS mixed solution; s4, heating the COF / CS mixed solution to form COF / CS hydrogel, aging the COF / CS hydrogel at room temperature, and freeze-drying the COF / CS hydrogel to obtain the self-floating beta-ketoenamine covalent organic framework-chitosan aerogel adsorbent. The aerogel adsorbent disclosed by the invention has the characteristics of wide pH application range, high adsorption capacity and easiness in recovery in the aspect of recovering noble metals in wastewater, and particularly shows high-selectivity adsorption on Au.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbents, and in particular to a self-floating beta-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent and a preparation method and application thereof. Background Art

[0002] At present, in order to achieve efficient and selective recovery of precious metal resources, a variety of technologies such as ion exchange, solvent extraction, membrane separation, electrodeposition and adsorption have been developed. Among them, the adsorption method is considered to be one of the most effective recovery methods due to its advantages such as simple operation, low cost and high separation efficiency. However, since the solution after electronic waste treatment is highly acidic and the concentration of competing ions is high, the stability and selectivity of the adsorption material are required to be high. In addition, the recovered precious metal ions also need to be desorbed, reduced and other operations to obtain metal elements, which further increases the complexity and cost of the recovery steps. Summary of the invention

[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to propose a self-floating β-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent and a preparation method and application thereof. The adsorbent prepared by the method can convert light energy into heat energy under illumination conditions, achieve stable and rapid selective adsorption of precious metals, and has a wide pH range of application, making it very suitable for efficient recovery of precious metals in electronic waste.

[0004] The method for preparing a self-floating β-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent of the present invention comprises the following steps:

[0005] S1, preparation of TpPa-1-COF nanoparticles;

[0006] S2, ultrasonically dissolving CS in an acetic acid aqueous solution to obtain a CS acetic acid aqueous solution;

[0007] S3, ultrasonically dispersing the TpPa-1-COF nanoparticles in ultrapure water, and then uniformly mixing the COF aqueous solution and the CS acetic acid aqueous solution to obtain a COF / CS mixed solution;

[0008] S4. The COF / CS mixed solution is heated to form a COF / CS hydrogel, aged at room temperature, and freeze-dried to obtain a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent.

[0009] Furthermore, the specific operation of step S1 is: fully grind p-phenylenediamine and p-toluenesulfonic acid, mix them evenly, add 1,3,5-trialdehyde-2,4,6-phloroglucinol, continue grinding, add water, continue grinding and heat for a period of time, grind and wash the obtained mixture, and vacuum dry it overnight to obtain TpPa-1-COF nanoparticles.

[0010] Furthermore, in step S2, the volume ratio of acetic acid to water is 3:625.

[0011] Furthermore, in step S2, the concentration of the CS acetic acid aqueous solution is 12.5 mg / mL.

[0012] Furthermore, in step S3, the mass volume ratio of TpPa-1-COF nanoparticles to ultrapure water is 50 mg:1 mL.

[0013] Furthermore, in step S3, the mass ratio of TpPa-1-COF nanoparticles to CS is 1-4:1-4.

[0014] Furthermore, in step S4, the reaction temperature is 70° C. and the reaction time is 2 hours.

[0015] Furthermore, in step S5, the room temperature aging time is 24 hours, and after pre-freezing in a -40°C cold trap for 2 hours, the water molecules in the gel network are removed by freeze drying for 24 hours to obtain a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent.

[0016] A self-floating beta-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent prepared by the above-mentioned preparation method.

[0017] An application of the self-floating β-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent as described above is used to recover precious metals in wastewater under light conditions.

[0018] Furthermore, the noble metal is Au.

[0019] The present invention combines chitosan (CS) aerogel with β-ketoenamine covalent organic framework TpPa-1 to prepare a composite aerogel material. TpPa-1 is a β-ketoenamine COF, which contains abundant soft base C=O bonds and N atoms in its framework and can be protonated to present positive charge (protonated functional group C=OH + and -NH2 + - / -NH3 + ), can adsorb precious metals through electrostatic, coordination and reduction effects. At the same time, the abundant -NH2 on CS has a certain reducing effect on precious metals, and the aerogel material formed by combining with COF can significantly improve the adsorption capacity and recovery performance of precious metals.

[0020] The aerogel adsorbent prepared by the present invention not only retains the excellent chemical stability of TpPa-1, but also inherits the overall and light characteristics of CS aerogel. The overall light aerogel is not only easy to separate from the water body, but also can float on the water surface, thereby efficiently absorbing sunlight. The thermal effect generated by light absorption not only accelerates the molecular thermal motion in the surrounding solution, promotes the aggregation of precious metal ions in the solution to the aerogel, and is conducive to adsorption; it can also reduce the adsorbed precious metal ions to metal elements through photocatalysis, thereby achieving efficient adsorption and recovery of precious metals.

[0021] The aerogel adsorbent prepared by the present invention exhibits a wide pH range, high adsorption capacity and easy recovery in the recovery of precious metals in wastewater, especially for Au, showing high selective adsorption. Under light conditions, the aerogel floating on the water surface can effectively absorb sunlight, and the photothermal effect prompts the aerogel to quickly adsorb precious metal ions, and the photocatalytically adsorbed precious metal ions are reduced to metal elements.

[0022] The present invention provides a method for synthesizing a self-floating aerogel material with mild reaction conditions, simple process and low energy consumption, which is easy to mass produce. The cost of CS is only 0.5 yuan / gram, which is much lower than the price of TpPa-1 (about 80 yuan / gram). Composite with COF can greatly reduce the cost of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the synthesis and application of the COF / CS aerogel adsorbent of the present invention;

[0024] Figure 2 This is a scanning electron micrograph of the TpPa-1 / CS-50% aerogel prepared in Example 2;

[0025] Figure 3 Fourier transform infrared spectra of the COF prepared in Example 1 and the TpPa-1 / CS-50% aerogel prepared in Example 2;

[0026] Figure 4 X-ray diffraction patterns of the COF prepared in Example 1 and the TpPa-1 / CS-50% aerogel prepared in Example 2;

[0027] Figure 5 Nitrogen adsorption-desorption spectra of COF prepared in Example 1 and TpPa-1 / CS-50% aerogel prepared in Example 2;

[0028] Figure 6 Schematic diagram of the TpPa-1 / CS-50% aerogel prepared in Example 2 adsorbing Au(III) under light, thermal imaging of the aerogel under light, and optical images of the aerogel after adsorbing and reducing Au(III);

[0029] Figure 7 This is a comparison chart of the adsorption efficiency of Au(III) by TpPa-1 / CS-50% aerogel prepared in Example 2 under light / dark conditions and TpPa-1 powder under dark conditions at different pH values;

[0030] Figure 8 This is a relationship diagram of the adsorption capacity of Au(III) under light / dark conditions of the TpPa-1 / CS-50% aerogel adsorbent prepared in Example 2 and the influence of adsorption time;

[0031] Fig. 9 This is a graph showing the relationship between the adsorption capacity of Au(III) of the TpPa-1 / CS-50% aerogel adsorbent prepared in Example 2 under light / dark conditions and the influence of solution concentration;

[0032] Fig.10 The selective adsorption performance of the TpPa-1 / CS-50% aerogel adsorbent prepared in Example 2 for different metal ions under light conditions;

[0033] Fig.11 This is a relationship diagram of the effect of illumination time on the surface temperature of a series of TpPa-1 / CS aerogel adsorbents prepared in Example 2 under illumination conditions;

[0034] Fig.12 This is a comparison chart of the adsorption performance of a series of TpPa-1 / CS aerogel adsorbents prepared in Example 2 for Au(III) at different pH values ​​under illumination conditions. DETAILED DESCRIPTION

[0035] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0036] Example 1

[0037] Preparation of β-ketoenamine COF nanoparticles by mechanical grinding: 0.45mmol 2,5-diaminobenzenesulfonic acid (Pa-1, 48.6mg) and 2.5mmol p-toluenesulfonic acid monohydrate (PTSA, 475.5mg) were fully ground for 5 minutes. After mixing evenly, 0.3mmol 1,3,5-trialdehyde-2,4,6-phloroglucinol (Tp, 63mg) was added and grinding was continued for 5 minutes. Then 100μL water was added and grinding was continued for 10 minutes. Then, the mixture was transferred to a glass vial and heated at 170℃ for 3 to 5 minutes. After grinding the obtained mixture into fine pieces, it was washed with hot water, N,N-dimethylacetamide and hot water in sequence, and vacuum dried at 60℃ for 12 hours to obtain COF-TpPa-1.

[0038] Example 2

[0039] like Figure 1 As shown in Figure 1, β-ketoenamine COF / CS aerogel was synthesized by chemical crosslinking combined with freeze drying: 10 mg CS was weighed and dissolved in 800 μL acetic acid aqueous solution (V 乙酸 :V 水 =3:625), ultrasonically treated for 20 to 30 minutes until completely dissolved, 10 mg TpPa-1 was weighed and added to 200 μL ultrapure water, ultrasonically treated for 10 to 15 minutes to make it evenly dispersed, the two solutions were mixed, vortexed for 15 to 20 minutes to form a uniform suspension, and then reacted at 70°C for 2 hours to obtain COF / CS hydrogel, which was aged at room temperature for 24 hours, pre-frozen in a cold trap for 2 hours, and freeze-dried for 24 hours to obtain TpPa-1 / CS aerogel, i.e., a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent.

[0040] The masses of TpPa-1 and CS were adjusted to prepare a series of COF / CS aerogels containing different proportions of TpPa-1.

[0041] 4 mg TpPa-1 and 16 mg CS prepared TpPa-1 / CS-20%;

[0042] 8 mg TpPa-1 and 12 mg CS prepared TpPa-1 / CS-40%;

[0043] 10 mg TpPa-1 and 10 mg CS prepared TpPa-1 / CS-50%;

[0044] 12 mg TpPa-1 and 8 mg CS prepared TpPa-1 / CS-60%;

[0045] 16 mg TpPa-1 and 4 mg CS prepared TpPa-1 / CS-80%.

[0046] Figure 2 This is a scanning electron micrograph of the TpPa-1 / CS-50% aerogel prepared in Example 2; Figure 2 It can be seen that the material as a whole presents a lamellar structure, and the COF particles are evenly embedded in the smooth aerogel surface.

[0047] Figure 3 Fourier transform infrared spectra of COF prepared in Example 1 and TpPa-1 / CS-50% aerogel prepared in Example 2; Figure 3 It can be seen that at 1582cm -1 、1453cm -1 、1260cm -1 The stretching vibration peaks at correspond to C=O bond, C=C bond, and CN bond, respectively, proving the successful synthesis of TpPa-1 powder and the successful embedding of TpPa-1 into aerogel material.

[0048] Figure 4 X-ray diffraction patterns of COF prepared in Example 1 and TpPa-1 / CS-50% aerogel prepared in Example 2; Figure 4 It can be seen that obvious diffraction peaks appear at 5° and 22°, corresponding to the characteristic diffraction peaks of the (100) crystal plane of TpPa-1 and CS, respectively, proving that TpPa-1 / CS-50% aerogel was successfully synthesized.

[0049] Figure 5 The nitrogen adsorption-desorption spectra of the COF prepared in Example 1 and the TpPa-1 / CS-50% aerogel prepared in Example 2; Figure 5 It can be seen that the specific surface area of ​​TpPa-1 / CS-50% aerogel is 108.1 m 2 / g, and still has a large specific surface area after being composited with CS, providing sites for the adsorption of precious metals.

[0050] Application Examples

[0051] The adsorption performance of TpPa-1 / CS aerogel adsorbent on Au(Ⅲ) under light was tested.

[0052] In this example, Au is selected as a representative of typical noble metals, and the photothermal performance and adsorption performance of the TpPa-1 / CS-50% adsorbent prepared in Example 2 are tested. The test steps are as follows:

[0053] (1) Prepare a solution with a concentration of Au(III) of 300 mg / L and adjust its pH to 1-8. Take 5 mg of TpPa-1 / CS-50% aerogel and place it in 20 mL of the solution. 2 ) and adsorb in the dark. Take the same mass of TpPa-1 powder and place it in 20mL solution for adsorption in the dark. After the adsorption is completed, the remaining concentration in the solution is tested, and the adsorption efficiency of Au(Ⅲ) by different materials under different conditions at different pH is calculated, such as Figure 7 As shown, the results showed that the adsorption efficiency of Au(Ⅲ) by TpPa-1 / CS-50% aerogel under light was significantly improved compared with that under dark conditions, and after TpPa-1 was composited with CS, it had a higher adsorption efficiency for Au(Ⅲ) than powdered TpPa-1.

[0054] Figure 6 Schematic diagram of the COF / CS aerogel prepared in Example 2 adsorbing Au(III) under light, thermal imaging of the aerogel under light, and optical image of the aerogel after adsorbing and reducing Au(III); Figure 6It can be seen that under light conditions, the surface temperature of TpPa-1 / CS-50% aerogel increased significantly, and gold particles were produced on the surface of the aerogel after adsorption, indicating that Au(III) was adsorbed and reduced to gold.

[0055] (2) Prepare a solution with a concentration of Au(III) of 200 mg / L and adjust its pH to 2. Place 5 mg of TpPa-1 / CS-50% aerogel in 20 mL of the solution and place it under xenon light (1 sun, 1000 W / m 2 ) Adsorb for 10 minutes, 20 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, and 8 hours. Oscillating adsorption in the dark for 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, 18 hours, and 24 hours. After the adsorption is completed, the remaining concentration in the solution is tested and the adsorption capacity of the material for Au(III) at different times is calculated, such as Figure 8 As shown, the results showed that TpPa-1 / CS-50% aerogel could reach adsorption equilibrium under light for 6 hours, which was significantly improved compared with dark conditions.

[0056] (3) Prepare solutions with Au(III) concentrations of 100, 200, 400, 600, 800, and 1200 mg / L, respectively, and adjust their pH to 2. Take 5 mg of TpPa-1 / CS-50% aerogel and place it in 20 mL of the solution. 2 ) for 6 hours. Oscillating adsorption in the dark for 24 hours. After the adsorption is completed, the remaining concentration in the solution is tested and the adsorption capacity of the material for Au(III) in solutions of different concentrations is calculated, such as Fig. 9 As shown in the figure, the maximum adsorption capacity of TpPa-1 / CS-50% aerogel for Au(Ⅲ) is 1470mg / g at 25℃ in the dark and 1575mg / g at 35℃. The thermal effect can increase the adsorption capacity. The maximum adsorption capacity of Au(Ⅲ) under light can reach 2035mg / g. The photothermal effect and photocatalytic synergy can significantly increase the adsorption capacity of TpPa-1 / CS-50% aerogel for Au(Ⅲ).

[0057] (4) Prepare a solution with a concentration of 5 mg / L Au(Ⅲ), 50 mg / L K(Ⅰ), Ni(Ⅱ), Cu(Ⅱ), Co(Ⅱ), Hg(Ⅱ), Cd(Ⅱ), Zn(Ⅱ), Al(Ⅲ), and Fe(Ⅲ), and adjust its pH to 2. Place 5 mg of TpPa-1 / CS-50% aerogel in 20 mL of the solution and place it under xenon light illumination (1 sun, 1000 W / m 2 ) for 6 hours. After the adsorption is completed, the residual concentration in the solution is tested and the adsorption capacity of the material for different metal ions is calculated, such as Fig.10As shown, the results showed that under light, TpPa-1 / CS-50% aerogel showed high adsorption selectivity for Au(III), with an adsorption rate higher than 98%.

[0058] 20 mg of TpPa-1 / CS aerogels of different ratios prepared in Example 2 were placed in 100 mL of ultrapure water and irradiated with a xenon lamp (1 sun, 1000 W / m 2 ) Use an infrared imager to record the temperature changes on the aerogel surface. Fig.11 As shown in the figure, the surface temperature of the aerogel increased significantly within 10 minutes of illumination. Because the interlayer stacking and open channels of COF enable it to effectively capture and transfer light energy during the photothermal conversion process and then convert it into heat energy, as the COF ratio increases, the surface temperature of the aerogel gradually increases, and the photothermal effect is conducive to the adsorption of precious metals.

[0059] (6) Prepare a solution with a concentration of Au(III) of 300 mg / L and adjust its pH to 2. Take 5 mg of TpPa-1 / CS aerogels with different COF ratios and place them in 20 mL of the solution. 2 ) was adsorbed for 6 hours. After the adsorption was completed, the residual concentration in the solution was tested and the adsorption capacity of Au(III) for aerogels with different COF ratios was calculated, as shown in Fig.12 As shown, the results showed that TpPa-1 / CS-50% had the highest adsorption capacity for Au(III).

[0060] The prepared COF / CS aerogel showed high adsorption capacity and excellent selectivity for Au(Ⅲ) in wastewater under light. TpPa-1 is a β-ketoenamine COF, which contains abundant soft base C=O bonds and N atoms in its skeleton, and protonated functional groups C=OH + and -NH2 + - / -NH3 + Under electrostatic action, AuCl4 - It is attracted to the surface of the adsorbent, and then further recovers Au(III) through the coordination of O in the C=O bond and the reduction of N atoms; CS has abundant amino groups, which have a certain reduction effect on Au(III). Therefore, the composite aerogel material obtained by COF and CS can increase the adsorption capacity of precious metals and improve the recovery performance. In addition, CS has low cost, and compounding with COF can greatly reduce the cost of the adsorbent.

[0061] The prepared COF / CS aerogel has high adsorption capacity and good selectivity, and is easy to separate from the solution after adsorption. The aerogel can float on the water surface and produce photothermal effect by absorbing sunlight, which increases its surface temperature, thereby accelerating the thermal motion of molecules in the surrounding solution, promoting the aggregation of precious metal ions to the aerogel, and improving the adsorption kinetic efficiency. In addition, the photocatalytic effect reduces the precious metal ions adsorbed on the surface of the material to precious metal elements, thereby realizing the economical and efficient recovery of precious metals.

[0062] For matters not mentioned above, the prior art applies.

[0063] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent, characterized in that: The steps include: S1, preparation of TpPa-1-COF nanoparticles; S2, ultrasonically dissolving CS in an acetic acid aqueous solution to obtain a CS acetic acid aqueous solution; S3, ultrasonically dispersing the TpPa-1-COF nanoparticles in ultrapure water, and then uniformly mixing the COF aqueous solution and the CS acetic acid aqueous solution to obtain a COF / CS mixed solution; S4. The COF / CS mixed solution is heated to form a COF / CS hydrogel, aged at room temperature, and freeze-dried to obtain a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent.

2. The preparation method according to claim 1, characterized in that: The specific operation of step S1 is: fully grind p-phenylenediamine and p-toluenesulfonic acid, mix them evenly, add 1,3,5-trialdehyde-2,4,6-phloroglucinol, continue grinding, add water, continue grinding, and heat for a period of time. After grinding and washing the obtained mixture, vacuum dry it overnight to obtain TpPa-1-COF nanoparticles.

3. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of acetic acid to water is 3:625; the concentration of the CS acetic acid aqueous solution is 12.5 mg / mL.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass volume ratio of TpPa-1-COF nanoparticles to ultrapure water is 50 mg:1 mL.

5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of TpPa-1-COF nanoparticles to CS is 1-4:1-4.

6. The preparation method according to claim 1, characterized in that: In step S4, the reaction temperature is 70° C. and the reaction time is 2 hours.

7. The preparation method according to claim 1, characterized in that: In step S5, the aging time at room temperature is 24 hours, and after pre-freezing in a -40°C cold trap for 2 hours, the water molecules in the gel network are removed by freeze drying for 24 hours to obtain a self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent.

8. A self-floating β-ketoenamine covalent organic skeleton-chitosan aerogel adsorbent prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the self-floating β-ketoenamine covalent organic framework-chitosan aerogel adsorbent as claimed in claim 8, characterized in that: Recover precious metals from wastewater under light conditions.

10. The use according to claim 9, characterized in that: The noble metal is Au.

Citation Information

Cited By

  • COF aerogel composite adsorption material for PFAS treatment as well as preparation method and application of COF aerogel composite adsorption material

    CN120365635A